2014
DOI: 10.1088/0031-9155/59/8/1963
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cerenkov emission as a quality assurance tool in electron radiotherapy

Abstract: A new potential quality assurance (QA) method is explored (including assessment of depth dose, dose linearity, dose rate linearity and beam profile) for clinical electron beams based on imaging Cerenkov light. The potential of using a standard commercial camera to image Cerenkov light generated from electrons in water for fast QA measurement of a clinical electron beam was explored and compared to ionization chamber measurements. The new method was found to be linear with dose and independent of dose rate (to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 25 publications
(28 reference statements)
6
86
0
Order By: Relevance
“…However, nuclear decay and nonelastic nuclear interactions can still create some Cerenkov light emission. Previously, we used Geant4 to determine the average light production of scintillation and Cerenkov emission when the scintillator was irradiated by a 60 MeV proton beam 25, 26. We found the relative production of Cerenkov emission compared to scintillation light was of the order 10 −5 .…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…However, nuclear decay and nonelastic nuclear interactions can still create some Cerenkov light emission. Previously, we used Geant4 to determine the average light production of scintillation and Cerenkov emission when the scintillator was irradiated by a 60 MeV proton beam 25, 26. We found the relative production of Cerenkov emission compared to scintillation light was of the order 10 −5 .…”
Section: Methodsmentioning
confidence: 97%
“…A 60 MeV proton beam is not capable of producing Cerenkov emission directly 25, 26. However, nuclear decay and nonelastic nuclear interactions can still create some Cerenkov light emission.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] It was concluded that the Cherenkov emission is suitable for surface dosimetry applications. 7 In the present paper, we suggest the use of Cherenkov radiation produced by relativistic electrons for investigation of optical properties of human tissues.…”
Section: Introductionmentioning
confidence: 99%